Optimization of obtaining the high label single strain probe based on the M13 phage - Telegeev, G.D.; Dybkov, M.V.; Kiyanitsa, K.N. (Биополимеры и клетка, 1995)
A method is proposed to obtain high-label single strain probe on the basis of the M13 phage. This is based on the use of a specific primer and the procedure of purification of the synthesized probe using nitrocellulose.